Does Good School Governance Role in The Performance Of School Operational Assistance Fund Management? - Sohidin, Sohidin; Rahmawati, Rahmawati; Djuminah, Djuminah; Gantyowati, E (Universitas Muhammadiyah Magelang, 2023)
Good school governance can improve the performance of school operational assistance fund management. This research aims to provide empirical evidence of the role of good school governance in the performance of school active assistance fund management. The study consists of 238 State Vocational High Schools in Central Java from 2019 to 2021. The research method used is quantitative, and primary data is obtained from the questionnaire responses of School Operational Assistance fund managers. The purposive sampling technique is used with a total of 952 respondents. Data processing and hypothesis testing are conducted using moderate regression analysis with the help of SPSS. This research has several novelties, including performance measurement based on 12 school operational assistance fund expenditure components. The results show that good school governance positively influences the performance of school active assistance fund management, except for indicators X7 (effectiveness and efficiency) and X8 (consensus-oriented))